Linear array Yagi-Uda 5G antenna for vehicular application - Sreelakshmi, K; Bora, Pronami; Mudaliar, Mona; Baburao Dhanade, Yuvraj; T.P Madhav, B (International Journal of Engineering and Technology, 2017)
A two element 2X2 linear array Yagi antenna which is meant to operate at frequency of 3.5GHz which can be used for low band 5G as well as for WIMAX is presented in this paper. This array consists of two radiating elements of eight parasitic elements each with overall dimensions of 110Ã—60Ã—1.6mm3. The proposed antenna was built on Rogers Duroid substrate. It exhibits a good bandwidth (impedance bandwidth of single antenna element about 600Mhz.for S11 less than-10dB at the center frequency of 3.5 GHz) and gain of 10.5dB. The idea behind this paper is to attain good gain along with bandwidth which can be utilized for vehicular applications.